General Overview on Nontuberculous Mycobacteria, Biofilms, and Human Infection. (4th November 2015) - Faria, Sonia; Joao, Ines; Jordao, Luisa
Abstract : Nontuberculous mycobacteria (NTM) are emergent pathogens whose importance in human health has been growing. After being regarded mainly as etiological agents of opportunist infections in HIV patients, they have also been recognized as etiological agents of several infections on immune-competent individuals and healthcare-associated infections. The environmental nature of NTM and their ability to assemble biofilms on different surfaces play a key role in their pathogenesis. Here, we review the clinical manifestations attributed to NTM giving particular importance to the role played by biofilm assembly.